The Past, Present, and Future Distribution of Sargentodoxa: Perspectives From Fossil Record and Species Distribution Models - Xuanqi Liu; Huasheng Huang; Xia Meng; Minqiao Li; Zeyu Qin (Ecology and Evolution)
ABSTRACT Global climate change is a critical factor influencing biodiversity and ecosystem stability by altering the suitable habitats of many species. Sargentodoxa cuneata is an endemic and relict plant species in China. Identifying its suitable habitats across different periods and glacial refugia helps explain how S. cuneata survived Quaternary climate fluctuations, which is crucial for informing its future conservation. However, long‐term tracking of its distribution and systematic description of biogeographical evolution remain scarce. Here, we compare 10 species distribution models to assess their predictive performance. Ultimately, we apply a random forest model to simulate the suitable habitats of S. cuneata under past, present, and future climate scenarios and integrate fossil records to analyze its biogeographical history. We find that S. cuneata once had a much broader distribution, likely originating in North America, with subsequent migration to Europe and Asia, and its range has gradually contracted, now primarily persisting in East Asia. It is currently distributed mainly south of the Qinling‐Huaihe Line in China, particularly in mid‐ and low‐altitude mountainous regions with abundant precipitation and moderate temperatures. During the Last Glacial Maximum (LGM, ~22,000 years ago) and Mid‐Holocene (MH, ~6000 years ago), its suitable habitat contracted significantly, with extremely suitable areas nearly disappearing due to colder climate. Glacial refugia are identified in three mountain ranges within Central and South China. Model simulations under two different climate scenarios suggest that while the total suitable habitat of S. cuneata may expand, extremely suitable areas could decline, with a northward expansion and southern contraction. This study will provide insights into the long‐term impact of climate change on relict plant species and contribute to a better understanding of the evolutionary history of East Asian flora.